Lone pair-π interactions in biological systems: occurrence, function, and physical origin - Kozelka, Jiří (European biophysics journal, 2017)
Lone pair-π interactions are now recognized as a supramolecular bond whose existence in biological systems is documented by a growing number of examples. They are commonly attributed to electrostatic forces. This review attempts to highlight some recent discoveries evidencing the important role which lone pair-π interactions, and anion-π interactions in particular, play in stabilizing the structure and affecting the function of biomolecules. Special attention is paid to studies exploring the physical origin of these at first glance counterintuitive interactions between a lone pair of electrons of one residue and the π-cloud of another. Recent theoretical work went beyond the popular electrostatic model and inquired the extent to which orbital interactions have to be taken into account. In at least one biologically relevant case-that of anion-flavin interactions-a substantial charge-transfer component has been shown to operate.
Keywords: π interactions; Models, Molecular; Anion–π interactions; biofyzika; Electrons; molekulární modely; Donor–acceptor systems; elektrony; Biophysics; Ab initio calculations; Energy decomposition analysis; Lone pair–π interactions; statická elektřina; Static Electricity